Fastabiqul khairat driven corporate philanthropy as sustainable business practices for organizational resilience - Mhd. Sarif, Suhaimi (KLIBEL, 2015)
Most businesses used short term business practices to gain long term profitability and competitive advantage. In reality, businesses are facing dynamic challenges and uncertainties. The sustainable business practices enable business continuity and resilience. This paper argues fastabiqul khairat driven corporate philanthropy helps businesses to be more resilient. Fastabiqul khairat is to be competitive and unstoppable in giving charity with the motivation, drive, energy and reinforcement to do good deeds for the sake of stakeholders. Fastabiqul khairat promotes long term practices for long term benefits. The existing shortterm corporate philanthropy justifies the reputation of socially responsible businesses but lack of organizational resilience. Businesses with good reputation and ability to deliver superior value gain better performance and competitive advantage. The study used personal interview with 10 social entrepreneurs to obtain feedback on the practices of fastabiqul khairat in the corporate philanthropy for social enterprises. The results of the study suggest that the practice of fastabiqul khairat is operationalized under the infaq (judicious spending) through the payment of zakat, corporate donation, and sponsorship on various social activities that linked with business activities. Business owners, strategists and decision makers should introduce fastabiqul khairat corporate philanthropy in business processes and strategies. Nevertheless, the results of the study cannot be generalized due to the specific contexts of the respondents which may be different from other contexts. The future study should consider more social entrepreneurs as respondents of the study for more robust and comprehensive results.